Exchange rate pass-through in the Euro Area - Rajmund Mirdala (FIW - Research Centre International Economics, 2016)
Time-varying exchange rate pass-through effects to domestic prices under fixed euro exchange rate perspective represent one of the most challenging implications of the common currency. The problem is even more crucial when examining crisis related redistributive effects associated with relative price changes. The degree of the exchange rate pass-through to domestic prices reveals its role as the external price shocks absorber especially in the situation when the leading path of exchange rates is less vulnerable to the changes in the foreign prices. Adjustments in domestic prices followed by exchange rate shifts induced by sudden external price shocks are associated with changes in the relative competitiveness among member countries of the currency area. In the paper we examine exchange rate pass-through to domestic prices in the Euro Area member countries to examine crucial implications of the nominal exchange rate rigidity. Our results indicate that absorption capabilities of nominal effective exchange rates clearly differ in individual countries. As a result, an increased exposure of domestic prices to the external price shocks in some countries represents a substantial trade-off of the nominal exchange rate stability.
Keywords: C32; E31; F41; 330; exchange rate pass-through; inflation; Euro Area; VAR; impulse-response function